Interaction of coffee compounds with serum albumins. Part II: Diterpenes. (15th May 2016) - Guercia, Elena; Forzato, Cristina; Navarini, Luciano; Berti, Federico
Highlights: We have studied the binding of coffee diterpenes cafestol and 16- O -methylcafestol to human and bovine albumin. The diterpenes bind at the interplay between Sudlow site 1 and a fatty acid binding site of albumins. This unusual interaction leads to a significant change in the secondary structure of the proteins. This leads to an increased drug binding by albumin in the presence of coffee diterpenes. Abstract: Cafestol and 16- O -methylcafestol are diterpenes present in coffee, but whilst cafestol is found in both Coffea canephora and Coffea arabica, 16- O -methylcafestol (16-OMC) was reported to be specific of only C. canephora . The interactions of such compounds, with serum albumins, have been studied. Three albumins have been considered, namely human serum albumin (HSA), fatty acid free HSA (ffHSA) and bovine serum albumin (BSA). The proteins interact with the diterpenes at the interface between Sudlow site I and the fatty acid binding site 6 in a very peculiar way, leading to a significant change in the secondary structure. The diterpenes do not displace reference binding drugs of site 2, but rather they enhance the affinity of the site for the drugs. They, therefore, may alter the pharmacokinetic profile of albumin – bound drugs.